α-Galactosidase and Sucrose-Kinase Relationships in a Bi-functional AgaSK Enzyme Produced by the Human Gut Symbiont Ruminococcus gnavus E1 - Lafond, Mickael; Tauzin, Alexandra S.; Bruel, Laetitia; Laville, Elisabeth; Lombard, Vincent; Esque, Jérémy; André, Isabelle; Vidal, Nicolas; Pompeo, Frédérique; Quinson, Nathalie; Perrier, Josette; Fons, Michel; et al. (Frontiers in Microbiology, 2020)
In the human gut, plant alpha-galactosides belonging to the raffinose family oligosaccharides (RFOs) are commonly degraded by microbial alpha-galactosidases. Among them the RgAgaSK bifunctional enzyme - classified in the GH36 family - is produced by the intestinal Ruminococcus gnavus E1 symbiont. Although our previous work has shown that RgAgaSK enzyme contains a hydrolytic -galactosidase domain linked to an ATP dependent extra-domain specifically involved in the phosphorylation of the C6 hydroxyl group on the glucose residue of sucrose, the relationships between both catalytic domains remain poorly understood. Therefore, we investigated herein molecular determinants from the multi-modular structure of RgAgaSK that are involved in -galactosidase and kinase activities. Biochemical characterization of heterologously expressed enzymes either in full form or in separated domains revealed similar kinetic parameters. These results were supported by molecular modelling studies performed on the whole enzyme in complex with different RFOs. An anionic exchange chromatography analysis concluded that catalytic efficiency values decreased as the number of D-galactosyl moieties branched onto the oligosaccharide increased, suggesting a preference of RgAgaSK for RFO’s short chains. A wide prevalence and abundance study with a human metagenomic library showed a high prevalence of the RgAgaSK encoding gene whatever the medical status of the individuals. Finally, phylogeny and synteny studies of RgAgaSK revealed a spread of the Rgaga1 cluster in the human gut microbiome based on a common ancestor.